Nephroprotective Potential of Mesenchymal Stromal Cells and Their Extracellular Vesicles in a Murine Model of Chronic Cyclosporine Nephrotoxicity - Ramírez-Bajo, María José; Martín-Ramírez, Javier; Bruno, Stefania; Pasquino, Chiara; Banon-Maneus, Elisenda; Rovira, Jordi; Moya-Rull, Daniel; Lazo-Rodriguez, Marta; Campistol, Josep M.; Camussi, Giovanni; Diekmann, Fritz (Frontiers in Cell and Developmental Biology, 2020)
Background. Cell therapies and derived products have a high potential in aiding tissue and organ repairing and have therefore been considered as potential therapies for treating renal diseases. However, few studies have evaluated the impact of these therapies according to the stage of chronic kidney disease. The aim of this study was to evaluate the renoprotective effect of murine bone marrow mesenchymal stromal cells (BM-MSCs), their extracellular vesicles (EVs) and EVs-depleted conditioned medium (dCM) in an aggressive mouse model of chronic cyclosporine (CsA) nephrotoxicity in a preventive and curative manner. Methods. After 4 weeks of CsA-treatment (75 mg/kg daily) mice developed severe nephrotoxicity associated with a poor survival rate of 25%, and characterized by tubular vacuolization, casts, and cysts in renal histology. BM-MSC, EVs and dCM groups were administered as prophylaxis or as treatment of CsA nephrotoxicity. The effect of the cell therapies was analyzed by assessing renal function, histological damage, apoptotic cell death, and gene expression of fibrotic mediators. Results. Combined administration of CsA and BM-MSCs ameliorated the mice survival rates (6-15%), but significantly renal function, and histological parameters, translating into a reduction of apoptosis and fibrotic markers. On the other hand, EVs and dCM administration were only associated with a partial recovery of renal function or histological damage. Better results were obtained when used as treatment rather than as prophylactic regimen i.e. cell therapy was more effective once the damage was established. Conclusion. In this study, we showed that BM-MSCs induce an improvement in renal outcomes in an animal model of CsA nephrotoxicity, particularly if the inflammatory microenvironment is already established. EVs and dCM treatment induce a partial recovery, indicating that further experiments are required to adjust timing and dose for better long-term outcomes.